Tectonic evolution of the Red River basin and adjacent area (Vietnam) in Cenozoic era - Phach, Phung Van; Le , Duc Anh; Nguyen, Thi Hong Hanh; Golozubov, V. V.; S., Kasatkin (Vietnam Journal of Marine Science and Technology, 2023)
Based on the structural and tectonophysic analysis of data collected from outcrops around Tonkin Gulf and the results of analysis of seismic sections of the Red River basin, the four main successive tectonic phases with specific paleostress fields since the beginning of the Cenozoic era have been established. The first, middle Eocene-early Miocene (45–15.97 My) tectonic phase, with sub-latitudinal compression and sub-longitudinal extension, was accompanied by large-scale sinistral displacement of the Red River fault, the extension centers of the Red River basin and seafloor spreading of East Vietnam Sea. The second, middle-late of middle Miocene (13.82–7.25 My) tectonic phase, with sub-longitudinal compression and sub-latitudinal extension, has created a local depocenter N-S orientation; right-lateral strike-slip of the Red River fault and first inversion of the basin. The third late Miocene (~7.25-5.33 My BP) tectonic phase, with NE-SW compression, has caused a strong inversion in the Red River basin with strong uplift of some blocks and significant shrinkage of the RRB up to 15–20%. The fourth Quaternary-to-Recent tectonic phase, with NW-SE compression and NE-SW extension, appears in an appearance of the hydraulic system offset, the recent grabens of NW-SE direction, the earthquakes, and GPS data. Formation and development of the Red River basin were controlled by tectonic activities and closely connected to NW-SE trending fault systems of regional scale such as the Red River fault, Chay River fault, Lo River faults, as well the local faults such as the Ca River fault, Rao Nay River fault, Tha Khet - Da Nang fault. Some spectacular examples of tectonic activity can be seen in the geographic features of Vietnam, Laos, and Thailand, particularly the mountain ranges, such as the Truong Son (or Viet-Lao) belt. When it comes to the sea, the Red River fault becomes less active, while the other faults of the RRFS, like the Chay River and Lo River, play the leading role in the developing the Red River basin.